Manajemen Kepala Sekolah dalam Membentuk Karakter Siswa melalui Salat Duha di SMP Negeri 1 Soko Tuban Tahun Pelajaran 2020/2021 - Alvin Naela; Ahmad Suyanto (Proceedings of Annual Conference on Islamic Educational Management, 2021)
This paper is a research on the management of school principals in shaping the character of students through prayer at SMP Negeri 1 Soko Tuban. This writing method is descriptive qualitative using a field research approach (field research) through the method of observation, interviews, and documentation. The results of this study indicate that in shaping the character of students through duha prayer through (1) planning is carried out through 2 processes, namely compiling a program of activities and setting goals. (2) Organizing is carried out based on the Decree of the School Principal. (3) Implementation is carried out regularly every morning and in congregation and after the midday prayer students listen to lectures from the teacher. (4) Evaluation by looking at CCTV during the activity, assessing report cards, scoring, and observing changes in student behavior. From the results of the evaluation of the character formed by the duha prayer, namely discipline, honesty, responsibility, and courage. (5) Supporting factors in the formation of student character through duha prayer at SMP Negeri 1 Soko Tuban, namely adequate human resources (HR), complete school facilities and infrastructure, support from all school parties, parents, and the surrounding community, programmed activities, good cooperation between all parties, a high sense of togetherness and kinship. (6) The inhibiting factors are limited control from school after students leave school, the influence of social media, the diversity of student characters that is difficult to regulate, inadequate places for ablution, and a lack of student awareness.